BUILDING A TRAINING PROCESS HIGHLY QUALIFIED SKI RACERS AT THE FINAL STAGE OF PREPARATION FOR THE XXIV WINTER OLYMPIC GAMES IN BEIJING - Golovachev, A.I.; Kolykhmatov, V.I.; Shirokova, S.V.; Novikova, N.B. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the methodological direction of building the structure and content of the training process of highly qualified ski racers specializing in distance racing at the site of the final stage of preparation for the main start of the season. Methods and structure of the study. The work was attended by five cross-country skiers with qualifications from Master of Sports (MS) to Honored Master of Sports (WMS), who were on centralized training for 18 days in the conditions of the middle mountains (Passo de Lavace pass, altitude 1800-2000 m, Italy) at the final stage of preparation for the XXIV Winter Olympic Games 2022 in Beijing (China). The methodological basis for the construction of the training process was the assumption that the participation of leading athletes in a series of Tour de Ski races, followed by a five-day microcycle of a restorative character ensures the preservation of the effect of pre-stay in hypoxia conditions, which allows after 1 microcycle (MCC) of a retracting nature to begin high-intensity muscle activity of a developing nature already in 2 MCC. Results and conclusions. It has been established that when staying in mid-mountain conditions, an increase in the efficiency of the training process is achieved due to the complex effect of the following factors: functional systems of the body that provide muscle activity; 2) systemic application of strength-oriented training in the gym, preceding the performance of speed-strength and strength-oriented loads in special skiing vehicles; 3) increase in the share of high-intensity muscular work in the 2nd and 3rd MCC.